Combined ACL and Anterolateral Ligament Reconstruction Using an Adjustable-Loop Fixation Device: Surgical Technique - German Alejandro Jaramillo Quiceno MD; Paula Andrea Sarmiento Riveros MD; Camilo Partezani Helito MD, PhD; Ruben Dario Arias Perez MD, BS; Andre Giardino Moreira da Silva MD (SAGE Publishing, 2024)
Background: There are several techniques for the combined reconstruction of the anterior cruciate ligament (ACL) and the anterolateral ligament (ALL), but none have shown superiority. This study aims to present a surgical technique that theoretically reduces some of the risks reported in these procedures. Indications: The main indications for the ALL reconstruction include chronic ACL injuries, revision ACL reconstruction, acute ACL injuries in patients with high-grade pivot-shift (grades 2 or 3), patients involved in pivoting sports, and generalized ligament hyperlaxity or knee hyperextension. Technique Description: Hamstring tendon autografts are used for the ACL and ALL reconstruction; a common femoral ACL and ALL tunnel is made outside-in, making a short socket. A continuous looped hamstring tendon autograft attached to one button is used. The ACL is fixed with an adjustable-loop button. Through small incisions, the tibial fixation of both grafts is performed with bioabsorbable screws. Results: We present a 19-year-old professional soccer player with an acute ACL tear, with no associated meniscal or chondral lesions. Owing to his young age and high-risk sports practice, a combined ACL and ALL reconstruction was performed. The combined ACL and ALL reconstruction with a single femoral tunnel using the hamstrings tendons graft is a well-established procedure for ACL augmentation, reducing failure rates for certain risk groups, with excellent outcomes reported. The use of an adjustable-loop button on the femur is a viable option for this kind of reconstruction with postoperative stability comparable to the interference screw, classically used for this kind of reconstruction. Discussion/Conclusion: This technique has some advantages, such as the use of a short outside-in femoral socket, thus theoretically improving healing. In addition, this lowers the risk of lateral collateral ligament injury, and since the ileotibial band graft is not used, the risk of injuring the lateral inferior genicular vessels and the peroneal nerve is theoretically reduced. Besides, using an adjustable-loop cortical button in the femur can theoretically reduce potential complications such as screw migration, soft-tissue impingement, femoral-site pain, and implant removal. Finally, the reconstruction is done with small incisions, improving the aesthetic result and postoperative pain. Considering all the aforementioned factors, this technique theoretically offers some benefits. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.